MANAJEMEN SPIRITUAL DI PONDOK PESANTREN AL MUNAWWIR KRAPYAK YOGYAKARTA - Zamroni; Dian Arif Noor Pratama; Riswadi, Riswadi (Universitas Nurul Jadid, 2021)
This paper aims to analyze the mapping of spiritual management process in Pondok Pesantren Al-Munawwir Kolplek L Krapyak Yogyakarta. The type of research used is qualitatively descriptive with a case study approach. Data collection techniques used are interviews, observations and documentation. Spiritual management makes a bridge to the peak consciousness of human self existence in the vertical line called fitrah awareness, one consciousness that is tawhid. Management concept is understood not only to be empirical-rational by relying on the ability of the five senses and human intellectuality, but more deeply to the values of spirituality that are the main center in success with various aspects of life. The results showed that Pondok Pesantren Al Munawwir Kompleks L implemented a pesantren management system that emphasizes managerial and applies spiritual values in its management through programs realized to achieve more comprehensive and holistic goals, namely through 1) takhalli management; 2) tahalli management; 3) tajalli management.